Measurement and statistical modeling of BRDF of various samples - Zhang, Hanlu; Wu, Zhensen; Cao, Yunhua; Zhang, Geng (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
Based on the Torrance–Sparrow model, a modified and simplified five-parameter model is obtained. Multi-angle bistatic reflectance data of surfaces of various materials are fitted using this model. Genetic algorithm is used to optimize the parameters for the model. The results of the five-parameter model are in good agreement with experimental data which do not take part in fitting, and are close to the results of two-dimensional bidirectional reflectance distribution function (BRDF) models. The five-parameter model shows a good applicability to various rough surfaces with different surface optical properties. The five-parameter model can be used to construct a three-dimensional BRDF distribution based on the spatial experimental data, which may provide more information on light scattering from rough surfaces.
Optica Applicata, Vol. 40, 2010, nr 1, s. 197-208
Keywords: optyka; bidirectional reflectance distribution function (BRDF); modeling; measurement; light scattering